Synthetic small-molecule RNA ligands: future prospects as therapeutic agents. Issue 8 (8th May 2019) - Di Giorgio, A.; Duca, M.
Abstract : RNA is one of the most intriguing and promising biological targets for the discovery of innovative drugs in many pathologies and various biologically relevant RNAs that could serve as drug targets have already been identified. Abstract : RNA is one of the most intriguing and promising biological targets for the discovery of innovative drugs in many pathologies and various biologically relevant RNAs that could serve as drug targets have already been identified. Among the most important ones, one can mention prokaryotic ribosomal RNA which is the target of several marketed antibiotics, viral RNAs or oncogenic microRNAs that are tightly involved in the development and progression of various cancers. Oligonucleotides are efficient and specific RNA targeting agents but suffer from poor pharmacodynamic and pharmacokinetic properties. For this reason, a number of synthetic small-molecule ligands have been identified and studied upon screening of chemical libraries or focused design of RNA binders. In this review, we report the most relevant examples of synthetic compounds bearing sufficient selectivity to envisage clinical studies and future therapeutic applications with a particular attention for the main strategies that can be undertaken toward the improvement of selectivity and biological activity.